Multiple copy number variants of VC1 gene reveal single-copy expression as a key determinant of vicine content - Ugwuanyi, Samson; Makhoul, Manar; Golicz, Agnieszka A.; Obermeier, Christian; Snowdon, Rod J. (Frontiers in Plant Science, 2025)
Faba bean is a valuable legume crop desired globally for its high nutritional composition. However, the seed vicine and convicine (v-c) content reduces the nutritional quality of faba bean protein and can induce favism in susceptible individuals. Recently, VC1 gene, encoding a bi-functional riboflavin protein, was reported to initiate the v-c biosynthetic pathway in V. faba. In low v-c cultivars, a 2 bp insertion in this gene disrupts its function by causing a frameshift and premature stop codon. However, because v-c biosynthesis is only partially reduced, this suggests that additional genes may also be involved in the pathway. Here, we identify and investigate multiple tandem gene duplications at the VC1 locus. Our findings reveal that VC1 exhibits multiple structural variants and copy number variations, but its expression is independent of copy number. Low v-c genotypes carry both variants of the gene — with and without the 2 bp insertion — but only the variant with the insertion is expressed. In contrast, high v-c genotypes consistently express the variant lacking the insertion. Although some high v-c genotypes also carry the insertion, it is found in a non-expressed variant, while the expressed variant lacks the insertion, resulting in the high v-c phenotype. We also report a novel diverging VC1 homolog, RIBA2, which shares expression domains with VC1. This homologous gene encodes GTP cyclohydrolase II, a critical enzyme in the v-c pathway. Expression of this gene contributes ~5-10% of riboflavin gene transcripts in immature seeds suggesting it as a minor-effect candidate locus in v-c biosynthesis. Moreover, two SNPs within the coding sequence of RIBA2 segregated with v-c content, offering a reliable alternative for marker-assisted selection in faba bean breeding. In conclusion, this study contributes to the elucidation of the complex genetic regulation of v-c biosynthesis and provides valuable insights to facilitate further efforts in its reduction in faba bean.